2007
DOI: 10.1074/jbc.m701937200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Phosphorylation of Collagen XVII by Ecto-Casein Kinase 2 Inhibits Ectodomain Shedding

Abstract: Ecto-phosphorylation is emerging as an important mechanism to regulate cellular ligand interactions and signal transduction. Here we show that extracellular phosphorylation of the cell surface receptor collagen XVII regulates shedding of its ectodomain. Collagen XVII, a member of the novel family of collagenous transmembrane proteins and component of the hemidesmosomes, mediates adhesion of the epidermis to the dermis in the skin. The ectodomain is constitutively shed from the cell surface by metalloproteinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Production of Abs to candidate neoepitopes on the shed ectodomain of collagen XVII Based on previously described candidate cleavage sites on collagen XVII (19)(20)(21), four different short peptides, 7-9 aa in length, and with nonblocked N termini, were prepared (Fig. 1A).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Production of Abs to candidate neoepitopes on the shed ectodomain of collagen XVII Based on previously described candidate cleavage sites on collagen XVII (19)(20)(21), four different short peptides, 7-9 aa in length, and with nonblocked N termini, were prepared (Fig. 1A).…”
Section: Cell Culturementioning
confidence: 99%
“…One study used protein extracted from normal human skin and suggested N-terminal cleavage at Ala 531 (19 in immortalized HaCat keratinocyte and DJM-1 cell lines (20). In addition, structural modeling of ADAM17 with phosphorylated collagen XVII predicted Leu 540 to be a cleavage site (21). In contrast, a further study showed that a mAb with an epitope within the amino acid stretch of Ser 515 to Arg 523 recognized the shed ectodomain of collagen XVII (22), indicating that ectodomain shedding of collagen XVII could occur at different position(s), probably in a context-dependent manner.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, some of extracellular matrix proteins are known to be phosphorylated [26,[30][31][32]. Yalak and Vogel identified 770 different phosphorylation sites in 66 extracellular proteins or in proteins with extracellular domain by annotation of secreted phosphorylated protein data available in public repositories [33].…”
Section: Protein Phosphorylation 140mentioning
confidence: 99%
“…The serine 544 in the extracellular domain of collagen XVII is phosphorylated by CK2 and the phosphorylation inhibits shedding of the extracellular domain by metalloproteases of the A disintegrin and metalloproteinase (ADAM) family [32]. Although the exact function of collagen XVII is unknown, collagen XVII is expressed in the CNS and its distribution is changed in neurodegenerative disorders [63].…”
Section: Collagen XVIImentioning
confidence: 99%